6(x-2)-8x=-26

Simple and best practice solution for 6(x-2)-8x=-26 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(x-2)-8x=-26 equation:


Simplifying
6(x + -2) + -8x = -26

Reorder the terms:
6(-2 + x) + -8x = -26
(-2 * 6 + x * 6) + -8x = -26
(-12 + 6x) + -8x = -26

Combine like terms: 6x + -8x = -2x
-12 + -2x = -26

Solving
-12 + -2x = -26

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '12' to each side of the equation.
-12 + 12 + -2x = -26 + 12

Combine like terms: -12 + 12 = 0
0 + -2x = -26 + 12
-2x = -26 + 12

Combine like terms: -26 + 12 = -14
-2x = -14

Divide each side by '-2'.
x = 7

Simplifying
x = 7

See similar equations:

| y+4=2x+6 | | 0.50x+0.15(50)=34.5 | | 2(0)+3y=36 | | 1.4x^2+.9x-31.7=0 | | (x-3)+3x+(x-1)=61 | | xy^3-16xyz^3= | | 2x-10=6-9x | | 2(-x+3)-5=9 | | 39/949 | | 3(8x-1)+7(x+5)=-59 | | 9=-6w+3(w-6) | | 4=12-d | | 15k=k-2 | | -7.6=0.4-4y | | 5x*5=180 | | 2.3x=12 | | 22=4(y+8)-6y | | -7/8x=49 | | -15r=r-7 | | -2+15+x=-4+8 | | 11x+66=21 | | 12=9-c | | 5x+2x+6x= | | 4(n+2)+3(2n+6)= | | 75+64+x=180 | | 7=3m+1 | | 2y+3y=30x | | a(2ab-5c)= | | 2x+y-3x=1 | | 2x-3(-2x+22)=-130 | | 3j+4=10 | | 201=17b+99 |

Equations solver categories